Functional Nanostructures for Sensors, Optoelectronic Devices and Drug Delivery - Castriciano, Maria Angela (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Nanoparticles and nanostructured materials represent an active area of research and impact in many application fields. The recent progress obtained in the synthesis of nanomaterials, and the fundamental understanding of their properties, has driven significant advances for their technological applications. The Special Issue "Functional Nanostructures for Sensors, Optoelectronic Devices and Drug Delivery" aims to provide an overview of the current research activities in the field of nanostructured materials with a particular emphasis on their potential applications for sensors, optoelectronic devices and biomedical systems. The Special Issue includes submission of original research articles and comprehensive reviews that demonstrated or summarized significant advances in the above-mentioned research fields. The Special Issue is made up of fifteen original research articles and three comprehensive reviews covering various topics of nanostructured materials and relative characterization from fundamental research to technological applications. More than 100 scientists from universities and research institutions lent their expertize and shared their research activities to ensure the success of this Special Issue.